Model Problem-Based Learning: Implementasi Pada Pembelajaran Matematika Materi Persamaan Dan Pertidaksamaan Linear - Jovanca Claudia Durian; Santje M. Salajang; Ichdar Domu (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to determine the difference in student learning outcomes regarding linear equations and inequality taught using the PBL model compared to student learning outcomes taught using the Direct Instruction model. This research is quasi-experimental. The samples in the research were class X-IPA as an experimental class with a total of 17 students. The instrument used in this research consisted of a learning outcomes test in the form of a written test in the form of an essay with material on linear equations and inequalities. The data collection technique is through observation and tests in the form of evaluation questions. The test is carried out twice. Namely, the pretest is carried out at the beginning of the research to determine students' achievement scores before treatment, and the posttest is carried out in both control and experimental groups after treatment. Based on hypothesis testing using independent test statistics (T-test), tcount = 3.596 and ttable = 1.694 at a significance level of ⍺ = 0.05. The research results show that the tcount value is more significant than ttable because (3.596 > 1.694) with a sig (2-tailed) value of 0.014 < 0.05 so it can be said that there is a significant difference in the learning outcomes of the experimental group using the PBL model and the control group using the Direct Instruction learning model which means that there is an influence of the application of the PBL learning model on the learning outcomes of class X students at SMA Negeri 2 Tondano.